EPSTEIN-BARR VIRUS AND NASOPHARYNGEAL CARCINOMA: VIRAL MARKERS FOR DIAGNOSTICS AND ASSESSMENT OF CLINICAL STATUS OF PATIENTS - V. N. Kondratova; M. V. Lomaya; A. V. Ignatova; T. E. Dushenkina; K. V. Smirnova; A. M. Mudunov; A. V. Lichtenstein; V. E. Gurtsevitch; N. B. Senyuta (Вопросы вирусологии, 2018)
The etiological role of the Epstein-Barr virus (EBV) in the development of an undifferentiated histological variant of nasopharyngeal carcinoma (uNPC) found for the first time in regions with a high incidence of this pathology, the Southern provinces of China and the countries of Southeast Asia, and later in the rest of the world, has served as a basis for the widespread use of EBV serological markers for the diagnosis of this form of tumor. In recent years, the use of a test based on the quantitative determination of the EBV DNA concentration in the blood plasma of uNPC patients for early detection and monitoring of the disease has become widespread in endemic regions. In non-endemic regions, such studies virtually have not been carried out, and moreover, the comparative evaluation of the significance of two viral markers, serological and EBV DNA load in the bloodstream of uNPC patients, for diagnostics and evaluation of the therapeutic effect was not investigated. The aim of this study was to compare the clinical value of two serological markers and plasma EBV DNA load in uNPC patients from non-endemic region (Russia). The obtained results indicate that IgA antibodies to the viral capsid antigen (IgA/VCA) and plasma EBV DNA concentration can be successfully used for the diagnosis of uNPC, while IgG/VCA antibodies have no practical significance as an uNPC marker. In addition, it was found that plasma EBV DNA load is more sensitive marker of uNPC than IgA/VCA titers because DNA copy numbers reflect more accurately the effect of the therapy and the clinical state of patients at the stages of remission or relapse. It was shown for the first time that in the non-endemic region the simultaneous evaluation of IgA/VCA antibody levels and the plasma EBV DNA loads are the most effective markers for the diagnostics of uNPC. However, we believe, that it is more practical to use IgA/VCA antibody levels for uNPC screening, and plasma EBV DNA copies - for monitoring of the disease.